FROM WATER CRISIS TO ENERGY OPPORTUNITY: THE URGENT NEED FOR DIVERSIFICATION IN KYRGYZSTAN’S ENERGY SECTOR - Aidana Satybaldieva (Western European Studies, 2026)
Kyrgyzstan’s electricity sector is overwhelmingly dependent on hydropower, which accounts for approximately 90 % of total electricity generation (International Energy Agency [IEA], 2023). While hydropower has historically underpinned energy security and enabled lowcarbon electricity production, increasing water scarcity, seasonal variability, and climateinduced glacier retreat pose growing risks to system reliability (World Bank, 2022; UNECE, 2023). These vulnerabilities are particularly critical given rising electricity demand and limited flexibility within the existing generation mix
Keywords: Paris Agreement; Nationally Determined Contribution; hydropower dependence